2013
DOI: 10.1093/jrr/rrt089
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of interfractional prostate motion in patients immobilized in the prone position using a thermoplastic shell

Abstract: The aim of this study was to evaluate the interfractional prostate motion of patients immobilized in the prone position using a thermoplastic shell. A total of 24 patients with prostate calcifications detectable using a kilo-voltage X-ray image-guidance system (ExacTrac X-ray system) were examined. Daily displacements of the calcification within the prostate relative to pelvic bony structures were calculated by the ExacTrac X-ray system. The average displacement and standard deviation (SD) in each of the left–… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…One study examined the use of prostatic calcifications as natural, internal fiducials for tracking with a kilovoltage X-ray IG system (ExacTrac® X-ray system; BrainLab Inc., Feldkirchen, Germany). 26 In this study, the required PTV margins were found to be 1.4, 9.7 and 6.1 mm in the LR, SI and AP directions, respectively. Although the ability to use intrinsic fiducials is attractive, not all patients have such calcifications, and the PTV margins seem larger (6-10 mm) than in other IG strategies.…”
Section: Immobilization Optionsmentioning
confidence: 53%
“…One study examined the use of prostatic calcifications as natural, internal fiducials for tracking with a kilovoltage X-ray IG system (ExacTrac® X-ray system; BrainLab Inc., Feldkirchen, Germany). 26 In this study, the required PTV margins were found to be 1.4, 9.7 and 6.1 mm in the LR, SI and AP directions, respectively. Although the ability to use intrinsic fiducials is attractive, not all patients have such calcifications, and the PTV margins seem larger (6-10 mm) than in other IG strategies.…”
Section: Immobilization Optionsmentioning
confidence: 53%
“…33 When considering the interfractional prostate motion in patients who are immobilized, the smallest movement occurs in the LR direction and the maximal displacement of .10 mm is observed only in the superior-inferior (SI) direction. 34 The variation in pancreas position during quiet breathing is closely linearly correlated with external abdominal movement. 31 Even though intrafractional pancreatic motion, which is induced principally by respiration, has the highest amplitude (,20.6 mm) in the CC direction, the AP (,10.1 mm) and LR (,6.7 mm) movements are also important.…”
Section: Organ Motionmentioning
confidence: 99%
“…The concept of the BTV was first suggested in 2000 [14], but it was considered difficult to achieve a BTV boost at that time because it was difficult to reproduce the BTV position with skin markings or bone matching using on-board kV imaging. The BTV position at the time of treatment often deviates from the position in the simulation CT due to interfractional error derived from the amount of urine and rectal gas present (e.g., [24]). Recently, cone-beam computed tomography (CBCT) on a linear accelerator has become more common, and organ-matching using CBCT can be widely implemented.…”
Section: Discussionmentioning
confidence: 99%